2012
DOI: 10.1088/0004-637x/751/2/102
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosynthesis and the Inhomogeneous Chemical Evolution of the Carina Dwarf Galaxy

Abstract: The detailed abundances of 23 chemical elements in nine bright RGB stars in the Carina dwarf spheroidal galaxy are presented based on high resolution spectra gathered at the VLT and Magellan telescopes. A spherical model atmospheres analysis is applied using standard methods (LTE and plane parallel radiative transfer) to spectra ranging from 380 to 680 nm. Stellar parameters are found to be consistent between photometric and spectroscopic analyses, both at moderate and high resolution. The stars in this analys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
240
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(272 citation statements)
references
References 137 publications
29
240
3
Order By: Relevance
“…also include, for comparison, Galactic stars from the compilation of Venn et al (2004;and references therein) and Milky Way dSph satellites including the more luminous dSphs (Shetrone et al 2001(Shetrone et al , 2003(Shetrone et al , 2009Fulbright et al 2004;Sadakane et al 2004;Geisler et al 2005;Aoki et al 2009;Cohen & Huang 2009;Frebel et al 2010a;Letarte et al 2010;Tafelmeyer et al 2010;Lemasle et al 2012;Venn et al 2012;and Starkenburg et al 2012) and the most recent measurements in a few ultrafaint dSphs (K08; Feltzing et al 2009;Frebel et al 2010b;Norris et al 2010b;Simon et al 2010;and Gilmore et al 2013). The Ba abundances and limits are very low, at a mean [Ba/H] of −3.97 from the three EW measurements, and [Ba/H] < −3.84 (2σ), <−3.55 (3σ), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…also include, for comparison, Galactic stars from the compilation of Venn et al (2004;and references therein) and Milky Way dSph satellites including the more luminous dSphs (Shetrone et al 2001(Shetrone et al , 2003(Shetrone et al , 2009Fulbright et al 2004;Sadakane et al 2004;Geisler et al 2005;Aoki et al 2009;Cohen & Huang 2009;Frebel et al 2010a;Letarte et al 2010;Tafelmeyer et al 2010;Lemasle et al 2012;Venn et al 2012;and Starkenburg et al 2012) and the most recent measurements in a few ultrafaint dSphs (K08; Feltzing et al 2009;Frebel et al 2010b;Norris et al 2010b;Simon et al 2010;and Gilmore et al 2013). The Ba abundances and limits are very low, at a mean [Ba/H] of −3.97 from the three EW measurements, and [Ba/H] < −3.84 (2σ), <−3.55 (3σ), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Figures 14 and 7 show the dataset of Tafelmeyer et al (2010) with green triangles for Sextans and blue triangles for Fornax. The Ursa Minor population is shown by purple stars (Cohen & Huang 2010), while the two Carina stars from Venn et al (2012) are seen in pink circles. We indicate in Fig.…”
Section: Comparison Samples: References Symbols and Colour Codes Inmentioning
confidence: 99%
“…The similarity in all measured elements between the two stars is striking and raises the possibility of a common origin. There are a number of low [α/Fe] stars known (Ivans et al 2003;Venn et al 2012), but none shares so many identical features. Aoki et al (2014) rightly pointed out that very low carbon abundances are found in highly evolved red giants and are often interpreted as the result of internal extra-mixing.…”
Section: To Be or Not To Be Pair-instablementioning
confidence: 99%
“…Norris et al 1997b;Aoki et al 2002;. 2010a) is shown as a black arrow and upper limits for Carina stars from (Venn et al 2012) are shown as gray arrows. Stars from other dwarf galaxies are shown as open gray circles (Fulbright et al 2004;Cohen & Huang 2009;Tafelmeyer et al 2010;Norris et al 2010b,a;Honda et al 2011;Lai et al 2011). So far studies of small samples of (extremely) metal-poor stars in dwarf galaxies have only found a few carbon-rich stars (Norris et al 2010a;Honda et al 2011;Lai et al 2011), as illustrated in Fig.…”
Section: Carbonmentioning
confidence: 99%
“…On the other hand, some of these studies show evidence for inhomogeneous mixing, resulting in significant chemical variations within these small systems at the lowest metallicities and/or highest ages. There are also indications of different abundance ratios for heavy elements of stars in the lowest mass systems (Frebel et al 2010b;Tafelmeyer et al 2010;Venn et al 2012).…”
Section: Introductionmentioning
confidence: 99%